CO2-assisted hydrolytic hydrogenation of cellulose and cellulose-based waste into sorbitol over commercial Ru/C - Polidoro, D; Stamilla, G; Feltracco, M; Gambaro, A; Perosa, A; Selva, M (Green Chemistry, 2023)
A single-step protocol was developed for the hydrolytic hydrogenation of microcrystalline cellulose into sorbitol over commercial carbon-supported Ru, in the presence of gaseous CO2 as an acid source and molecular hydrogen as a reductant. Under these conditions, cellulose was first hydrolysed to glucose by reversibly formed carbonic acid in water and then instantaneously hydrogenated on Ru/C. By tuning the reaction parameters, such as temperature, time and the relative pressure of CO2 and hydrogen gas, cellulose was fully converted at 220 & DEG;C in 18 h under 30 and 40 bar of H-2 and CO2, respectively, with a sorbitol yield of 81%. Blank experiments revealed that without a catalyst and hydrogen, the reaction exhibited <5% conversion and glucose was the only detected product when the reaction was performed under CO2 pressure. XRD measurements on CO2-treated cellulose surprisingly revealed no noticeable changes in the crystallinity index (<10% with respect to microcrystalline cellulose), suggesting that hydrolytic hydrogenation took place on crystalline, not amorphous, cellulose. Furthermore, not only several cellulosic feedstocks, including filter paper, cotton wool, and cotton fiber, but also typical cellulose-based wastes such as a cardboard pizza box were also tested and under the optimized conditions sorbitol was obtained with yields ranging from 56% up to 72% in all cases. No less significant was the Ru/C catalyst stability, which could be recycled at least six times without any noticeable activity loss.